Targeted Use of Sustainable Aviation Fuel to Maximize Climate Benefits - Teoh, Roger; Schumann, Ulrich; Voigt, Christiane; Schripp, Tobias; Shapiro, Marc; Engberg, Zebediah; Molloy, Jarlath; Koudis, George S.; Stettler, Marc E. J. (Environmental Science & Technology, 2022)
Sustainable aviation fuel (SAF) can reduce aviation’s CO2 and non-CO2 impacts. We quantify the change in contrail properties and climate forcing in the North Atlantic resulting from different blending ratios of SAF and demonstrate that intelligently allocating the limited SAF supply could multiply its overall climate benefit by factors of 9-15. A fleetwide adoption of 100% SAF increases contrail occurrence (+5%), but lower nonvolatile particle emissions (-52%) reduce the annual mean contrail net radiative forcing (-44%), adding to climate gains from reduced life cycle CO2 emissions. However, in the short term, SAF supply will be constrained. SAF blended at a 1% ratio and uniformly distributed to all transatlantic flights would reduce both the annual contrail energy forcing (EFcontrail) and the total energy forcing (EFtotal, contrails + change in CO2 life cycle emissions) by ~0.6%. Instead, targeting the same quantity of SAF at a 50% blend ratio to ~2% of flights responsible for the most highly warming contrails reduces EFcontrail and EFtotal by ~10 and ~6%, respectively. Acknowledging forecasting uncertainties, SAF blended at lower ratios (10%) and distributed to more flights (~9%) still reduces EFcontrail (~5%) and EFtotal (~3%). Both strategies deploy SAF on flights with engine particle emissions exceeding 1012 m-1, at nighttime, and in winter.